Pro SharePoint solution development : combining .NET, SharePoint and Office 2007 - Hild, Ed.; Adams, Susie (Berkeley, Calif. : Apress ; New York : Distributed to the book trade worldwide by Springer-Verlag New York, 2007)
The latest versions of the microsoft office desktop tools and application servers provide an incredible number of features and functionality out of box.They integrate more strongly than any previous release.
Includes index.
ma 06/03/2018
Keywords: Intranets (Computer networks); Web servers